Spectral broadening in tight confinement geometry of a random fiber laser - Sarmani, Abdul Rahman; Al-Alimi, Abdulmoghni Ali Wazae; Yusoff, N. Mohd; Mahdi, Mohd Adzir (Elsevier BV, 2022)
We present a random Raman fiber laser pumped by a continuous-wave 1480nm source where neither a visible saturable absorber nor a fiber Bragg grating were incorporated. The backward pumping feedback loop allows a single direction of 1584nm wave propagation under tighter confinement of a dispersion compensating fiber (DCF). This geometry that implies a stronger Kerr-lensing effect supports two types of nonlinear broadening that were achieved in the stable output power generation. The first that agrees well to wave kinetics theory favors 1.76 to 3.53nm spectral progress. Against this flow, another type of wider broadening begun at 4.88nm before reducing gradually to 4.05nm with the increase in pump power. The former corresponds to a maximum of 6.3 times broadening ratio with respect to the pump linewidth. To date, this is the best achievement in the world at just below 1.7 W pump power level especially without utilizing pump-pulse synchronization or any external mode-locking modulations. In contrast without the tighter confinement geometry, the initiation of 4.25nm bandwidth was realized in the unstable power zone. These ascertain the double roles of dispersion compensating fiber as a stabilizing factor as well as for dispersion management.